(untitled) (Journal of Surgical Sciences, 2022)
Background: Conventional continuous closure or mass closure for abdominal closure with monofilament non- absorbable Polypropylene is one of the widely used standard techniques. Hughes repair named after Professor Leslie Hughes, is a combination of one horizontal and two vertical mattress sutures in a single suture where load is distributed along the incision length as well as across it. Objective of this study include comparing post-operative wound complications in Hughes abdominal repair and those with that by conventional continuous closure in midline abdominal incision in emergency laparotomy. Methods: This study was conducted in the Department of Surgery & Casualty, Chattogram Medical College Hospital, Bangladesh between May 2018 and April 2019. Study population included 39 patients in Group A whom Abdomen was closed by Hughes abdominal repair and 39 patients in Group B in whom Abdomen was closed by conventional continuous closure. Results: Four (10.3%) patients had wound infection in group A and six (15.4%) in group B. Two (5.1%) patients had partial wound dehiscence in group A and six (14.4%) in group B. The difference of wound infection and partial wound dehiscence were found statistically not significant. Two patients had burst abdomen in group A and nine in group B, which was found statistically significant (p<0.05). Mortality rate was zero for both groups in the present study. Mean time to stay in hospital was 9.59 ± 4.756 days in Group A and 14.77 ± 9.042 days in Group B respectively. The difference was statistically significant (p<0.05) between two groups. Conclusion: Hughes abdominal repair of vertical midline abdominal incision showed a better result on the patients who underwent in emergency laparotomy and was found to be associated with a low incidence of serious complications. Journal of Surgical Sciences (2022) Vol. 26(1) : 42-48